Otthein Rammstedt and the Bliss of Sociability - Vernik, Esteban Jorge (2020)
Early one morning in fall of 2002, I met Otthein Rammstedt and Angela Rammstedt at the Buenos Aires airport. In the evening, I picked them up at their hotel, and we walked a few blocks before going into a bar. Professor Rammstedt ordered us each a Campari and orange juice (one part Campari to three parts juice, the formula—he explained—used in many Italian cities for evening aperitifs). From the moment the drinks came until well after midnight, we talked nonstop about Simmel. For the most part, I asked questions and Rammstedt provided generous and thorough responses, sometimes with the encouragement of Angela. Our conversation began with Simmel’s travels in Italy, and then his essay on the experience of sharing spiritual meals and drinks1 . It continued with possible Spanish-language editions of Simmel’s works, and culminated with the idea of doing a sociological study of the current Cuban embargo according to Simmel’s theory of conflict...